2022
DOI: 10.1111/joim.13596
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolite profiles linking dietary patterns with health—Toward precision nutrition

Abstract: Diet is one of the most important exposures that may affect health throughout life span. Investigations on dietary patterns rather than single food components are gaining in popularity because they take the complexity of the whole dietary context into account. Adherence to such dietary patterns can be measured by using metabolomics, which allows measurements of thousands of molecules simultaneously. Derived metabolite signatures of dietary patterns may reflect the consumption of specific groups of foods or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 115 publications
(194 reference statements)
0
7
0
Order By: Relevance
“…Our study adds to existing literature by demonstrating a possible time-dependency effect of an Unhealthy dietary pattern on child neurodevelopmental outcomes, using both maternal and child self-reported dietary intakes, and objective metabolome-derived modelling. Many studies have found strong dietary signatures in the metabolome, suggesting this may be a promising avenue for personalised nutrition and targeted therapeutic strategies (28).…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds to existing literature by demonstrating a possible time-dependency effect of an Unhealthy dietary pattern on child neurodevelopmental outcomes, using both maternal and child self-reported dietary intakes, and objective metabolome-derived modelling. Many studies have found strong dietary signatures in the metabolome, suggesting this may be a promising avenue for personalised nutrition and targeted therapeutic strategies (28).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 46% of the blood metabolites are related to the intestinal microbiome [75]. For the third viewpoint: (ⅲ) Lactobacillus can regulate the activity of the immune system, reduce inflammation, and promote the absorption and utilization of nutrients, which can have an impact on the metabolites in the blood [49,[76][77][78]. As the beta-diversity analysis showed, there were significant differences between the groups of CON, L. pentosus YQ001 and L.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, some of the metabolite profiles identified with dietary patterns [39][40][41], lifestyle behaviors [42,43], and lifestyle scores [16] have been related to the risk of various chronic conditions [19,20]. For example, in PREDIMED, a metabolic signature that robustly reflects adherence and metabolic response to a Mediterranean diet prospectively predicts the risk of CVD risk Table 3 Hazard ratio (95% CIs) for incident T2D and CVD using the metabolomic signatures of the HL score as categorical or continuous variables in the T2D and CVD nested case-cohort studies independently of traditional risk factors in both Spanish and US cohorts [18].…”
Section: Discussionmentioning
confidence: 99%